Epigenetic BET reader inhibitor apabetalone (RVX-208) counters proinflammatory aortic gene expression in a diet induced obesity mouse model and in human endothelial cells. (January 2023) - Wasiak, Sylwia; Tsujikawa, Laura M.; Daze, Emily; Gilham, Dean; Stotz, Stephanie C.; Rakai, Brooke D.; Sarsons, Chris D.; Fu, Li; Azhar, Salman; Jahagirdar, Ravi; Sweeney, Michael; Johansson, Jan O.; et al.
Abstract: Background and aims: Obese patients are at risk for type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). A lipid-rich diet promotes arterial changes by inducing hypertension, oxidative stress, and inflammation. Bromodomain and extraterminal (BET) proteins contribute to endothelial and immune cell activation in vitro and in atherosclerosis mouse models. We aim to determine if BET inhibition can reduce lipid-rich diet-induced vascular inflammation in mice. Methods: Body weight, serum glucose and lipid levels were measured in mice fed a high-fat diet (HFD) or low-fat diet (LFD) for 6 weeks and at study termination. BET inhibitors apabetalone and JQ1 were co-administered with the HFD for additional 16 weeks. Aortic gene expression was analyzed post necropsy by PCR, Nanostring nCounter® Inflammation Panel and bioinformatics pathway analysis. Transcription changes and BRD4 chromatin occupancy were analyzed in primary human endothelial cells in response to TNFα and apabetalone. Results: HFD induced weight gain, visceral obesity, high fasting blood glucose, glucose intolerance and insulin resistance compared to LFD controls. HFD upregulated the aortic expression of 47 genes involved in inflammation, innate immunity, cytoskeleton and complement pathways. Apabetalone and JQ1 treatment reduced HFD-induced aortic expression of proinflammatory genes. Congruently, bioinformatics predicted enhanced signaling by TNFα in the HFD versus LFD aorta, which was countered by BETi treatment. TNFα-stimulated human endothelial cells had increased expression of HFD-sensitive genes and higher BRD4 chromatin occupancy, which was countered by apabetalone treatment. Conclusions: HFD induces vascular inflammation in mice through TNFα signaling. Apabetalone treatment reduces this proinflammatory phenotype, providing mechanistic insight into how BET inhibitors may reduce CVD risk in obese patients. Graphical abstract: Image 1 Highlights: The HFD induced pro-inflammatory gene expression and TNFα signaling in the aorta of DIO mice. BET protein inhibitors apabetalone and JQ1 reduced proinflammatory aortic gene expression in DIO mice. HFD-sensitive genes are induced by TNFα in human endothelial cells and suppressed by apabetalone. Apabetalone could mitigate vascular inflammation in obese patients.